2016
DOI: 10.1007/s00198-016-3713-5
|View full text |Cite
|
Sign up to set email alerts
|

CYP2R1 polymorphisms are important modulators of circulating 25-hydroxyvitamin D levels in elderly females with vitamin insufficiency, but not of the response to vitamin D supplementation

Abstract: This study showed a difference in 25(OH)D levels between CYP2R1 genotypes that equates a daily supplementation of 400-800 IU vitamin D, depending on genotype. It underscores possible important genetic contributions for the high prevalence of hypovitaminosis D in the Middle East.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…Seasonal variations of vitamin D are well described, with lower serum 25(OH)D levels in the winter, except for countries from the Gulf states, where they are lower in the summer due to longer in-door dwelling to avoid the scorching heat. In addition, genetic factors, namely polymorphisms in key genes of the vitamin D pathway, modulate vitamin D status in western populations and possibly the Middle East ( Wang et al, 2010 ; Ahn et al, 2010 ; Arabi et al, 2017 ). The recognition of these consistent predictors justifies vitamin D supplementation strategies to prevent progression to symptomatic osteomalacia or rickets, which although becoming increasingly rare, is certainly not extinct in the region.…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal variations of vitamin D are well described, with lower serum 25(OH)D levels in the winter, except for countries from the Gulf states, where they are lower in the summer due to longer in-door dwelling to avoid the scorching heat. In addition, genetic factors, namely polymorphisms in key genes of the vitamin D pathway, modulate vitamin D status in western populations and possibly the Middle East ( Wang et al, 2010 ; Ahn et al, 2010 ; Arabi et al, 2017 ). The recognition of these consistent predictors justifies vitamin D supplementation strategies to prevent progression to symptomatic osteomalacia or rickets, which although becoming increasingly rare, is certainly not extinct in the region.…”
Section: Discussionmentioning
confidence: 99%
“…However, 25‐OH‐vitamin D3 serum levels were not significantly different between men and women probably because of small sample size with a low number of MS male. Several Authors showed that subjects carrying the AA genotype of rs10766197 CYP2R1 SNP have lower vitamin D levels compared to subjects carrying the GG genotype, after adjustment for potential predictors, including age, season and sex (Arabi et al, ; Barry et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D deficiency is characterized by bone loss, increased risk of fractures, and bone mineralization defects, which may lead to bone-related diseases such as osteoporosis, osteopenia, and osteomalacia [1][2][3][4]. Moreover, genetic variants of vitamin D3-related genes are associated with abnormal bone turnover and metabolism of bone diseases [5][6][7][8]. Vitamin D3 supplements are essential treatments for the prevention of bone loss, which underlies the mechanisms for decreasing bone resorption by osteoclasts and increasing bone formation by osteoblasts [9].…”
Section: Introductionmentioning
confidence: 99%